The impact of lss, svc and am on impulsive buying in Tiktok Shop - Puspita, Nita; Muslih, Basthoumi; Damayanti, Susi (Proceeding ICAMEKA: International Conference Accounting, Management & Economics Uniska, 2025)
Affiliate Marketing against Impulsive Purchases on TikTok Shop. This research uses a quantitative approach using a correlational survey design with data collection through a Google Form-based questionnaire to students of the Management study program at Universitas Nusantara PGRI Kediri, with a purposive sampling technique a sample of 94 students was obtained. The analysis method used is the classical assumption test, multiple linear regression analysis, coefficient of determination test and hypothesis test processed using the SPSS 25 software application. The results of this research show that partially Live streaming Shopping has a positive and significant effect on Impulsive Purchases, then Affiliate Marketing also has a positive and significant effect on Impulsive Purchases while Short Video Content has no effect on Impulsive Purchases. However, simultaneously Live streaming Shopping, Short Video Content and Affiliate Marketing have a positive and significant effect on Impulsive Purchases